The Role of Discourse and Modal Markers in the Structure of Oral and Written Argumentation of College Students - Alonso Chacón, Paula (2025)
This article analyzes, on the one hand, the use of rhetorical movements that make up the structure of argumentation, in order to determine the influence of oral and written production on them. On the other hand, it analyzes the role of discourse and modal markers in this structure, in order to determine 1) whether these linguistic resources demarcate the openings of rhetorical movements and 2) which rhetorical movements are influenced by oral and written production. The sample is integrated by 72 analytical arguments –36 oral and 36 written–, produced by recently admitted college students concerning the topic of Higher education as a way to promote social equality. Once the texts were obtained, they were transcribed, segmented into clauses, and coded according to the proposed categories of analysis to identify the structure of the argumentation and the function of discourse and modal markers. The results showed the prevailing of the argumentative movements in favor and the argumentative movements against, and that the discursive markers as well as the modal ones frequently headed the opening of these rhetorical movements, especially in oral texts, which corroborates the role of markers as a mean to demarcate texts into argumentative and no argumentative discourse units.